Tafsir Ayat-Ayat Muqatha’ah Perspektif Al Mawardi: Telaah Surah Al-Baqarah Ayat 1 - Muhammad Ziaurrahman; Zaki Arif (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This article discusses the interpretation of the muqatha’ah verses, specifically Surah al-Baqarah verse 1, which begins with the letters Alif Lam Mim, from the perspective of Abu Hasan al-Mawardi. The purpose of this study is to explore al-Mawardi’s understanding, approach, and contribution to the interpretation of these muqatha’ah letters, which have long been recognized as a unique linguistic and theological phenomenon in the Qur’an. This research employs a literature review method by analyzing al-Mawardi’s work An-Nukat wa al-‘Uyun and comparing it with the views of other classical mufassir (Qur’anic exegetes) regarding the muqatha’ah verses. The findings show that al-Mawardi offers diverse and profound interpretations, combining linguistic, numerical, and historical approaches to reveal the meanings behind these letters. His approach not only explains the muqatha’ah verses as signs of the greatness and miraculous nature of the Qur’an but also as an intellectual challenge for Muslims to understand the revelation more deeply. In conclusion, al-Mawardi’s interpretations enrich the classical tafsir tradition by opening a broad dialog on the symbolic meanings of the muqatha’ah verses. These findings are significant as a foundation for further research to explore the theological and rhetorical functions of the muqatha’ah verses in a modern context.